THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP TOWARD SERVICE EXCELLENT OF NURSES IN HOSPITAL - Alice Sutedjo Lisa; Sudiro - -; Farid Farid Agushybana (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Background: Patient satisfaction was one of the indicators of hospital service quality. Service excellent concept in hospital aimed to fulfill the patient expectation of hospital services. One of the factors which affect service excellent is leadership style. Objective:This research aimed to analyzed the relationship of transformational leadership style of the inpatient room head and service excellent practice of nurses in inpatient unit of Telogorejo Hospital. Method: This was observational research with cross sectional approach. Data collected using questionnaires. Sample was chosen with random sampling method and divided proportionally for each inpatient room as much as 184 respondents. Results: Research showed that idealized influence (p-value: 0,029), inspirational motivation (p-value: 0,037), intellectual stimulation (p-value: 0,018), individual consideration (p-value: 0,049) dimension from transformational leadership had significant relationship with service excellent practice of nurses in inpatient unit in Telogorejo Semarang Hospital. Conclusion: There were significant relationship between idealized influence, inspirational motivation, intellectual stimulation individual consideration of inpatient room head and service excellent of nurses in inpatient unit.Keywords: Transformational leadership, service excellent, nurse, hospital, patient expectation